Improving Students Speaking Ability Through Information Gap Teaching Technique (A Classroom Action Research at The Second Grade Students of MTs Al-Muhajirin Pacitan) - Neri Wijayanti (At-Ta'dib, 2018)
This study is aimed at describing the implementation of Information Gap teaching technique, describing whether or not Information Gap technique improves the students’ speaking ability and describing the students’ response on Information Gap teaching technique in teaching speaking. The study was implemented in MTs Al Muhajirin at the second grade, using action research. The researcher  took 40 students as the subject of  the research. The researcher teaches speaking English using Information Gap method. To find the results, the researcher got the information from the students’ answers on oral test in the form of  pre-test and post-test. The result of  the research using information gap shows  that, the researcher used the CAR (Class Action Research) principle to collect the data. The study consist of  two cycles with each cycle consist of four elements. By implementing Information Gap technique  in teaching speaking, the students have chance to be active and cooperative in teaching speaking. The mean of pre-test is 68,7, post-test is 71,6 and the improvement result of the implementation is  2,9. The students’ responses are positive. Most of  the students said  that they great this technique. They could easily learn English speaking. The students admitted  that their speaking was improved.